(untitled) (Economic and Political Thought, 2016)
The paper analyzes the practice of religious giving in Romania. In the first part the authors examine the recent scientific literature regarding the predictors of religious giving. Secondly, they quantitatively explore a data base of religious behavior corresponding to a Romanian national sample from 2011 using the R statistical software. Interpretation of the obtained results and conclusions are presented in the last part of the study.